O ensino de ciências e a Escola Nova: análise de interfaces entre história da ciência e ensino - Tonobohn, Elisabete (2010)
The aim of this paper is to analyze the Pioneers Manifesto from the New School, some of its assumptions and consequences in science teaching from 1930 until 1950. During this period Brazil represented a new political, economical and social model where Brazilian education would start to have a fundamental role in this new reorganization. The model proposed by the pioneers from the new school featuring: Anísio Teixeira, Lourenço Filho and Fernando de Azevedo, through the Pioneers Manifesto, showing the democratic principles of education for the entire nation. The performance of these three icons from the pioneers movement was based in the pragmatism philosophy of John Dewey about experimental education. Although pragmatism was expressed in the manifesto, we could identify in this model similar traces to the positivist ideas. Another important aspect from this paper was to try to relate the two currents: the positivism and the pragmatism in part of its conceptions. The approach possible to be verified was the sense of progress which both of them brought in each proposal. Not only the pragmatism but also the positivism had an idea of development, different perspectives, but the approach was made in valuing the science as an object of progress. These two currents presented importance when they dealt with education and science as fundamental elements for a nation progress. Campos reform in the beginning of the 30 s covered an ample part of the proposals presented by the pioneers, from public education from the kindergarten to the university, secular and democratic school. Science valorization or scientific knowledge as the beginning for the development, and the model present in this proposal was the one from John Dewey. Capanema reform changed secondary education in the country, but the historical background was also changed to a totalitarian regime and therefore it would not fit the defense of the movement principles, once the root of this movement was based in a democratic education as the way to learning. Although positivism had been the greatest influence in the end of XIX century and the beginning of the XX century, it was also present in this context. This statement is made because it would not be possible to have a sudden assimilation of another philosophy that influenced the historical, social and mainly the educational characteristics from the country. Having in mind the History of science we can consider an interface with teaching. It is a possibility to analyze how the scientific knowledge was being assimilated and spread through this process